Content Analysis of Human Resources Management Reporting Practices in Romanian Health Industry - Ana-Maria Bratu (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Questions - To what extent do the various corporate reporting channels, documents, and instruments incorporate the issues identified in the literature as affecting human capital? Which aspects are taken into account by Romanian healthcare companies regarding the reporting of human resources management practices? Motivation - Given the commitment of companies to sustainable development, the requirements for enhancing the reporting of human resource management practices have increased. In addition to the specific responsibilities of economic entities that are required to publish periodic financial statements, this study is particularly relevant to human resource management practices in Romanian companies. In this study, the focus is on companies in the healthcare sector, an industry sensitive to the events that have occurred in recent times. Idea - This study explores the defining elements of human resources management awareness and behaviour. The main objective of the research is to analyse the area of human resource information reporting in six companies in the healthcare or pharmaceutical sector and its debate in the context of different company characteristics. Data - To achieve the proposed objective, data from the annual reports were collected for 2021 for six Romanian companies listed on the Bucharest Stock Exchange. Tools - The extracted information is analysed through a critical interpretation to identify and analyse the level of reporting. In this study, the collected data was critically analysed based on empirical and archival sources to understand human resources reporting practices. All data used in this study were manually collected. Findings - The results of this research show that there is an interest in transparency of human resources information, but some variables should be improved or, where appropriate, added to the report. The most detailed information found is related to the reporting of descriptive company characteristics such as profitability and company size , and the least detailed is the information that belongs to the human resource category such as employment of people with disabilities and employment of women. Contribution - This paper contributes to research on companies' human resources reporting practices by identifying what is included in the annual report and analysing it through the lens of the transparency with which companies treat these practices.
Keywords: I11; J24; M41; 650; human resource management; healthcare industry; human resource accounting disclosure; Romania; annual reports